The association between the dietary inflammatory index (DII) and some serum oxidative stress markers in Non-Alcoholic fatty liver disease: Case- control - Fateme Moradi; Zahra Heidari; Azam Teimori; Mohammadreza Ghazvini; Zahra Faghih Imani; Amirmansour Alavi Naeini (International Journal of Preventive Medicine, 2022)
Purpose: Non-alcoholic fatty liver disease (NAFLD) is the most common liver disorder. The purpose of this study was to determine the relationship between the dietary inflammatory index (DII) and the serum oxidative stress markers in patients with NAFLD. Methods: In this case-control study, 121 patients with NAFLD and 119 healthy subjects were frequency-matched on gender. DII scores were calculated by using a 168-item food frequency questionnaire (FFQ). Blood samples were collected to measure serum oxidative markers. Linear regression and odds ratio (OR) were also used in this study. Results: The mean ± standard deviation of age for case and control group was 38.04 ± 6.7 and 35.6 ± 10.2, respectively. The gender ratio (female to male) for the case and control group was 1:1.42 and 1:1.38, respectively. The mean of the DII in the patient group was significantly higher than the healthy group, (P-values < 0.01). There was a significant negative relationship between TAC and DII (B = -2.63 (95%CI: -4.59, -0.68) and there was also a positive relationship between Malondialdehyde (MDA) and DII (B = 0.15 (95%CI: 0.02, 0.28) in the healthy group, but they were not significant in the case group. After multivariate adjustment, subjects in the most pro-inflammatory DII group had 73 times higher odds of NAFLD compared to subjects in tertile 1 (OR = 72.9; 95%CI (14.3-371.9)). Conclusions: Our findings suggest a direct association between the pro inflammatory properties of diet in patient and healthy group, but no relationship between TAC, MDA, and DII in the case group.